Diagnostic Accuracy of Spot Urine Protein-Creatinine Ratio for Pre-Eclampsia among Females Presented to Tertiary Level Hospital with Pregnancy-Induced Hypertension: Diagnostic Accuracy for Pre-Eclampsia - Khan, Aneela; Akhter, Ayesha; Humaira, Maryam; Hanif, Aasma; Anwar, Sadia; Chughtai, Sadaf; Naseer, Misbah (Pakistan Journal of Health Sciences, 2024)
Preeclampsia is main cause of fetal, maternal and newborn death globally, particularly in low- and middle-income nations. It's usually diagnosed when a pregnant woman shows indicators of hypertension and proteinuria. Objective: To determine diagnostic accuracy of spot urine protein-creatinine ratio (P/C ratio) for pre-eclampsia in females presenting with pregnancy induced hypertension, using 24-hour urine protein as gold standard, and to look for a correlation between spot urine P/C ratio and 24-hour urine protein. Methods: This was cross sectional study carried out at Department of Obstetrics and Gynecology, Sughra Shafi Medical Complex, Narowal from February 2024 to August 2024. 451 pregnant females after 20 weeks till delivery were admitted through OPD in ward. Simple Random sampling technique was used to collect data. All information was recorded through pre-designed Proforma regarding 24-hour urine collection and spot urine to P/C ration. Data were entered and analyzed by SPSS version 23.0. Spearman’s rank correlation coefficient was used to evaluate the relationship between the spot urine P/C ratio and 24-hour urine protein. A p-value <0.05 was considered statistically significant. Result: Spearman's correlation showed a strong positive correlation (r=0.82, p<0.05) between 24-hour protein and spot urine P/C ratio. Moreover, results showed a specificity of 87.8% (83.6%–91.9%), and sensitivity of 97.2% (94.9%–99.4%) based on clinical thresholds for proteinuria. Conclusions: The findings showed that urine P/C ratio might replace 24-hour urine protein for detecting proteinuria in preeclampsia. Additionally, it is a standardize, easy to execute and straightforward test and affordable with no requirement of systematic hospitalization.